Exploring Characteristics and Contributory Factors of Road Crashes and Near Misses Recorded via Dashboard Camera - Ariffin, A.H.; Solah, M.S.; Hamzah, A.; Ahmad, M.S.; Mohamad Radzi, M.A.; Zulkipli, Z.H.; Salleh, A.S.; Mohd Jawi, Z. (Journal of the Society of Automotive Engineers Malaysia, 2021)
The use of dashboard camera (dashcam), or also known as digital video recorder (DVR) is increasingly becoming popular among personal vehicle owners nowadays due to affordable prices and higher video qualities. Many road-related incidents including vehicle crashes and near-misses can be recorded using dashboard cameras and shared via social media as lessons learned to others. Recorded videos of the incidents in real-time can be observed and used for a variety of purposes, including as supportive evidence for investigation. This paper explores the potential use of recorded dashcam videos in determining the characteristics and factors contributing to road crashes and near-misses under different situations. Selected video records of road crashes and near-misses were obtained from the internet thru social media and were used for analysis. The findings concluded that a dashboard camera is an effective digital video technology for traffic and accident monitoring systems. It has a high potential in providing supportive evidence of many frequently occurring factors and understanding the causes of road crashes and near-miss incidents.